Factors associated with the symptoms of depression in people with heart failure - Débora Ananias de Melo; Maria Cristina Lins Oliveira Frazão; Gerlania Rodrigues Salviano Ferreira; Cleane Rosa Ribeiro da Silva; Lia Raquel de Carvalho Viana; Riane Barbosa de Lima; Katia Neyla de Freitas Macedo Costa (Cogitare Enfermagem)
Objective: Identify the factors associated with the symptoms of depression in people with heart failure.